The impact of anxiety and depression symptoms on people with multiple cardiovascular risk factors - Arévalo, Karla V.; Suárez, Esteven M.; Aldaz, Gina G.; Dávila, Luis P.; Calderón, Jeremy M.; Torres, Renato M.; Piedra, María F.; Chango , Carlos A. (International Journal of Research in Medical Sciences, 2024)
Typical cardiovascular risk factors are mainly related to lifestyle. New research suggests that psychological factors, especially anxiety and depression, are closely linked to cardiovascular factors. Anxiety and depression have shown an abysmal increase in the number of people who suffer from them in recent years. Different factors are related to their appearance, among which the social, work, emotional and environmental environment stand out. Multiple studies mention their relationship with cardiovascular risk factors, although there are multiple mechanisms associated with psychological and cardiovascular factors, to date there is no way to measure them. The impact of psychological stress on the development of different cardiovascular factors and its effect on the autonomic nervous system causing its inflammation must be investigated and requires much interest. As such, tools are required to be able to evaluate the biological pathways that link anxiety/depression with the risk of developing cardiovascular diseases.